Are intravaginal practices associated with human papillomavirus and the development of cervical cancer? A systematic literature review - Tafadziswa T Museba; Rebecca J Howett; Christine Campbell (Journal of Global Health Reports)
# Background Intravaginal practices (IVPs) are behaviours undertaken by women in diverse global settings for the promotion of hygiene and sexual health. Although evidence is inconclusive, it has been suggested that they may be harmful and associated with adverse gynaecological outcomes. The objective of this study was to investigate whether there is an association between IVPs, human papillomavirus (HPV) infection and the development of cervical cancer. As human immunodeficiency virus (HIV) infection may be a factor accelerating progression, recent evidence on the association between IVPs and HIV was also considered.